Repercussions of the COVID-19 pandemic on medical waste management - I Wayan Koko Suryawan; Aura Dhia Rizki Atthar; Mega Mutiara Sari; Iva Yenis Septiariva; Sapta Suhardono; Imelda Masni Juniaty Sianipar (International Journal of Public Health Science (IJPHS), 2022)
The COVID-19 pandemic is a global outbreak that also changes the generation of medical waste in hospital. The increasing number of people infected with the severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) virus indirectly requires the management of infectious waste from patients to be safe and not have the potential to spread. The purpose of this study was to analyze the medical waste management in a hospital located in Jakarta City, Indonesia. This study employed direct observation and used secondary data in the analysis. Meanwhile, to determine the effect of the population infected with SARS-Cov-2 on medical generation, One Way ANOVA analysis was used. Data from May, 2020 showed that medical waste generation increased from 25.6 kg/month to 192.3 kg/month. The ANOVA significance test showed a value of 0.013; this indicates that the number of the infected population significantly affects the generation of medical waste. Medical waste that found during a pandemic becomes more complex, including hazmat clothes, masks, gloves, medical headgear, used bandages, injection and infusion equipment, eating and drinking utensils for patients exposed to COVID-19, and used swab and rapid test equipment.